IMPLEMENTASI SISTEM ADMINISTRASI PEMBUATAN AKTA KELAHIRAN DALAM PENINGKATAN KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN JAYAWIJAYA - PAPUA - NUR AINI; TAUFIK RACHMAN (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The purpose of this study was to determine the quality of public services carried out by the Jayawijaya Regency Population and Civil Registration Service to the community. With service quality variables, and indicators: Tangible (physical evidence), Reliability (reliability), Responsivines (responsiveness), Assurance (guarantee), empathy (empathy). The data analysis technique used is descriptive qualitative data analysis with observation, interview and documentary methods analyzed using qualitative analysis. The data in this study were collected from primary data sources (primary data) and secondary data sources (secondary data). From the primary data source (primary data), the research informants were determined using purposive sampling and accidental sampling techniques. Sources of information on secondary data, obtained through literature and documents. In this study, researchers used data credibility and data confirmability techniques to test the validity of the data. Based on the research results, it is known that the physical evidence (tangible), namely, the facilities and infrastructure are already available although they are still inadequate. Service officers who will carry out service tasks to the community are still lacking. Officers in providing information about requirements to the community, not as expected. Reliability (reliability), it is known that there is a procedure, in the form of a flow chart displayed in the service room. There is a standard operating procedure used in providing services for making birth certificates. In completing the birth certificate, there is still no discipline. The absence of clear information about the service requirements provided by service personnel. Responsiveness (responsivines), regarding the certainty of service schedules, has been running according to established standards. The implementation of service standards, in making birth certificates, is neither fast nor precise. Officers do not listen to customer complaints regarding the completion of the birth certificate. Assurance, it is known that officers have not guaranteed the timeliness of completing documents, and empathy (empaty), that officers pay attention to customer interests, are in accordance with public service standards. The attitude of the officers in serving is polite.